Preoperative serum thyroglobulin predicts initial distant metastasis in patients with differentiated thyroid cancer. Issue 1 (December 2017) - Kim, Hosu; Kim, Young; Kim, Hye; Park, So; Choe, Jun-Ho; Kim, Jung-Han; Kim, Jee; Chung, Jae; Kim, Tae; Kim, Sun
Abstract Differentiated thyroid cancer (DTC) generally has a favorable prognosis. However, a small percentage of patients suffer from initial distant metastasis (DM). To date, there is no effective predictor for the presence of initial DM. The aim of this study was to determine if preoperative serum thyroglobulin (Tg) level could predict initial DM in DTC. We reviewed an institutional thyroid cancer database from October 1994 to February 2016. To determine the Tg cutoff for predicting initial DM, 4, 735 patients who were diagnosed with DTC were included in this study. Fifty-seven patients (1.2%) were identified as having DTC with initial DM. Median preoperative Tg level was 328.4 ng/ml in the initial DM group and 10.0 ng/ml in the non-DM group. Initial DM was the most important factor affecting serum Tg level (β  = 2, 049.32 ± 103.40;P  < 0.001). The Tg cutoff level that distinguished overall DM with the greatest accuracy was 63.4 ng/ml [area under the ROC curve 0.914, sensitivity 84.2%, specificity 90.6%, negative likelihood ratio (LR) 0.17, and positive LR 8.97]. Preoperative Tg levels were useful for predicting initial DM of DTC. Measurement of serum Tg in patients with DTC may guide preoperative staging evaluation and initial treatment.